Establishment of the first platelet-donor registry in Argentina - Blanco, Sebastián Gabriel (2020)
Background: Platelet transfusions are necessary to prevent and treat haemorrhages in thrombocytopenic patients or those with severe platelet dysfunction. In Latin American countries, including Argentina, blood supplies from voluntary non-remunerated blood donors remain dependent on family replacement donors, since altruistic repeat donors are exceptional and platelet donors are very scarce. The aim of this study was to recruit a group of frequent, voluntary, altruistic blood donors and determine their human platelet antigen (HPA)-genotype in order to establish the first registry of HPA-typed voluntary platelet donors in Argentina. Material and methods: In this study, we invited and recruited voluntary blood donors who attended the Fundación Banco Central de Sangre between July 2016 and July 2017. DNA was extracted from K2EDTA anticoagulated whole blood and genotyping was performed by polymerase chain reaction, using sequence-specific primers to type the HPA-1 to -6, -9 and -15 systems. A subset of samples was also tested using a commercial HPA-TYPE kit. Donors were invited to join the National Register of Haematopoietic Stem Cell Donors of Argentina. Results: A cohort of 500 platelet donors was recruited and characterised and a database with their personal information, including their genotype for the most relevant HPA alloantigens, was created. Eight of the 500 donors (1.6%) were HPA-1a negative. HPA allelic variants -4b, -6b and -9b were detected for the first time in our population. There was 100% concordance between our in-house assay and the commercial kits in the subset of 150 donor samples assayed in parallel. Discussion: The efforts made to recruit, characterise and register voluntary platelet donors will provide the first sustainable source of HPA and human leukocyte antigen-typed platelets for compatible transfusions in the country. Remarkably, we identified a higher percentage of HPA-1a-negative donors than previously detected in the Argentinean population.